Diagnostic Accuracy of PET/CT and Contrast Enhanced CT in Patients With Suspected Infected Aortic Aneurysms. (June 2020) - ,; Anagnostopoulos, A.; Hasse (PI), B.; Eberhard, N.; Hoffmann, M.; Husmann, L.; Kopp, R.; Ledergerber, B.; Rancic, Z.; Mestres, C.A.; Zbinden, R.; Zinkernagel, A.; et al.
Abstract : Objective: Infected aortic aneurysms are highly lethal, and management is very demanding, requiring an early diagnosis. The aim of this study was to evaluate the diagnostic accuracy of positron emission tomography/computed tomography with 18 F-fluorodeoxyglucose (PET/CT) and contrast enhanced CT (CE-CT) in patients with suspected infected aortic aneurysms. Methods: PET/CT was performed in patients with clinically suspected infected aortic aneurysms, and additional CE-CT was performed if feasible. Diagnostic accuracy was assessed by two independent readers using a four point grading score for both imaging modalities. Maximum standardised uptake values (SUVmax ) were calculated for quantitative measurements of metabolic activity in PET/CT. The reference standard was a combination of clinical presentation, laboratory findings, and imaging. Results: Ten patients were included prospectively in the study, 24 retrospectively; 16 patients (47%) prior to the start of antimicrobial treatment and all 34 patients prior to any vascular intervention. Thirteen of the 34 patients had an infected aortic aneurysm (38%). Proven infected aortic aneurysms were all metabolically active on PET/CT with a median SUVmax of 6.6 (interquartile range 4.7–21.8). Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of PET/CT for the diagnosis of infected aortic aneurysm was 100%, 71%, 68%, 100%, and 82%, for reader 1 and 85%, 71%, 65%, 88%, and 77%, for reader 2. Respective values for CE-CT, performed in 20 patients (59%), were 63%, 75%, 63%, 75%, and 70%, for reader 1 and 88%, 50%, 54%, 86%, and 65%, for reader 2. Conclusion: The diagnostic accuracy of PET/CT in the detection of infected aortic aneurysms ( n  = 13) is high, and higher than CE-CT. While PET/CT demonstrates an excellent sensitivity, its specificity is hampered because of false positive findings.